Youth as Subjects and Agents of Artistic Research: A Comparison of Youth-Engagement Models - Christie, Sheila (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
The iCreate Cape Breton pilot project sought to cultivate intergenerational networks of community artists and practitioners, with the long-term goal of empowering youth who face challenging economic or environmental circumstances. The three-year project began with recruitment of youth through established community organizations, followed by an initial phase of multidisciplinary creative exploration, during which youth worked closely with Cape Breton University faculty, as well as elders from their own communities. Phase One culminated in a public showcase of youth-led artistic projects, including theatre, music, film, and visual art, centred around the theme of slow violence. During Phase Two, young artists worked more independently, creating one feature film and two short documentaries. While the second-phase partnership model illuminated challenges around power dynamics, responsibilities, and expectations, it was more effective than the first-phase mentorship model with respect to empowering youth as research partners and facilitating long-term resiliency and social transformation.